Differentiation of the Left and Right Side Interventricular Septum Function in Healthy Subjects by Vector Velocity Imaging - Masoumeh Faghani Langroudi; Mahdi Nouri; Mohamad-reza Aghajankhah; Hassan Moladoust; Golshan Ghasemzadeh (Anatolian Journal of Cardiology, 2022)
Background: The present study aimed to assess and compare regional strain of the right and left sides of interventricular septum in healthy subjects using velocity vector imaging analysis due to the importance of interventricular septum and limited basic information about the exact function of the interventricular septum.